Targeted bone remodelling : investigating the scissors model - Dooley, Clodagh M. (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2013)
Bone is continually being removed and replaced through the actions of basic multicellular units (BMU). This constant upkeep is necessary to remove microdamage and thus maintain the integrity of the bone. Microdamage forms in bone naturally due to fatigue and manifests itself as an elliptically shaped crack with its long axis running parallel to the anisotropic grain of the bone. The repair process in bone is targeted, meaning that a BMU travels directly to the site of damage and repairs it. It is still unclear how targeted remodelling is stimulated and directed but it is highly likely that osteocytes play a role. A number of theories have been advanced to explain the microcrack osteocyte interaction but no complete mechanism has been demonstrated.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin